Patients of 75 years and over with ANCA‐associated vasculitis have a lower relapse risk than younger patients: A multicentre cohort study. (13th January 2022) - Thietart, Sara; Beinse, Guillaume; Smets, Perrine; Karras, Alexandre; Philipponnet, Carole; Augusto, Jean‐François; El Karoui, Khalil; Mesbah, Rafik; Titeca‐Beauport, Dimitri; Hamidou, Mohamed; Carron, Pierre‐Louis; Maurier, François; et al.
Abstract: Background: Little is known about antineutrophil cytoplasmic antibodies (ANCA)‐associated vasculitis (AAV) in older patients. We aim to study relapse risk of granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) in patients diagnosed after 75 years and compare it with those of patients aged 65–75 years. Methods: Data from AAV patients aged ≥65 years were extracted from the French Vasculitis Study Group (FVSG) database and from a call for observation to FVSG members. Cox and Fine–Gray models were used to assess relapse risk, taking death into account either as a censoring or a competing event, respectively. Results: The analysis included 219 patients aged ≥75 years (median 79) and 80 patients aged 65–75 years (median 70), of those 155 had GPA (52%), 136 MPA (45%), with 95 (32%) anti‐proteinase 3 positivity and 179 (61%) anti‐myeloperoxidase. Patients aged ≥75 years had a lower relapse risk in multivariate analysis (cause‐specific hazards ratio [CSHR] 0.54, 95% CI [0.33–0.89], p = 0.016, Cox model; subdistribution hazard ratio [SHR] 0.46, 95% CI [0.29–0.74], p = 0.001, Fine–Gray model) after taking into account vasculitis type. Patients aged ≥75 years had a lower probability of being treated for remission maintenance with a combination of glucocorticoids and immunosuppressants (vs. glucocorticoids alone, HR 0.28, 95% CI [0.11–0.68], p = 0.005) after adjusting to Five Factor Score, although relapse‐free survival was significantly longer when receiving such combination (CSHR 0.40, 95% [CI 0.24–0.67], p < 0.001). Conclusions: AAV patients ≥75 years have a lower relapse risk than patients aged 65–75 years despite a lower probability of having received maintenance therapy with a combination of glucocorticoids and immunosuppressants, but they still benefit from such treatment regimen. Abstract :